Occupational diseases in the automotive industry from medical and geographic viewpoints - comparison between the Czech Republic and the Slovak Republic - Jarolímek, Jan; Legáth, Ľubomír; Urban, Pavel (Central European journal of public health, 2019)
OBJECTIVE: The aim of the study was to compare the occurrence of occupational diseases (ODs) in the automotive industry in the Czech Republic and the Slovak Republic and to analyze their determinants. METHODS: The aggregated and anonymized data on ODs from the period 2001-2017 were used. A questionnaire survey was conducted in the Czech Republic (response rate 70.6%) and in the Slovak Republic (response rate 57%). The occurrence of ODs according to socioeconomic factors, the size of enterprises and their position in the global production networks was evaluated. The quality and scope of the occupational health services were also taken into consideration. RESULTS: Workers older than 40 years were at a significantly higher risk of ODs than the younger ones. In the Czech Republic, it corresponded to OR 2.77 (95% CI 2.41-3.19), in the Slovak Republic to OR 2.01 (95% CI 1.34-3.01). The risk of ODs in women was significantly higher than in men - in the Czech Republic it corresponded to OR 3.20 (95% CI 2.79-3.67), in the Slovak Republic to OR 2.43 (95% CI 2.05-2.87). The difference between the two states did not reach statistical significance in any of the studied factors. In both states, no ODs were reported from the microenterprises. CONCLUSION: Given the results of the study, it can be recommended to focus on the ergonomics of assembly work in the automotive industry. Special attention should be given to the provision of occupational health services, especially in microenterprises.
Keywords: Humans; lidé středního věku; Occupational Diseases; automobily; rizikové faktory; Female; dospělí; Automobiles; nemoci z povolání; lidé; zpracovatelský průmysl; Slovakia; Slovenská republika; automotive industry; Adult; occupational diseases; ženské pohlaví; Male; Middle Aged; incidence; Czech Republic; health geography; Česká republika; mužské pohlaví; Manufacturing Industry; Risk Factors